Antenna pattern scattering by rectangular cylinders. - Cheung, H.D (IEEE Transactions on antennas and propagation)
The uniform geometrical theory of diffraction (UTD) and the complex source point method are combined to predict two-dimensional (2-D) scattering by rectangular cylinders for E and H-polarized beam sources. Arrays of such beam solutions are also used to model propagation of radio beams into the shadow regions of buildings for local extended sources. Direct numerical verification of the results is obtained for square cylinders of moderate width